Does the Fit of Competitive Priorities Between Manufacturing and Marketing Function Matter? A Proposal - Md. Nor, Khalil (Faculty of Management and Human Resource Development, 2005)

(untitled)
In this paper, I propose a study to investigate the relationship between an organization’s performance and the fit of competitive priorities of manufacturing and marketing functions. There are two propositions in this study. First, organizations that exhibit a higher degree of fit of competitive priorities between their marketing and manufacturing functions will have a higher customer satisfaction compared to those that exhibit a lower degree of fit of competitive priorities between their marketing and manufacturing functions. Second, organizations that have higher customer satisfaction will have better financial performance compared to those that have lower customer satisfaction. I suggest manufacturing companies to be used as the sampling frame. Respondents are those who hold the top most position in manufacturing, marketing and finance departments. A simple regression can be used to analyze the data. I believe the proposed study will provide empirical support to show the importance of manufacturing and marketing functions subscribing to the same set of competitive priorities